Core-shell structured pt-w based catalysts, methods of making and using the same, and methods of selective hydrogenolysis
Patent Information
- Application Number
- CN202510557522.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明的目的是为了克服现有技术存在的催化剂的反应活性和水热稳定性较差,目标产物选择性较低,贵金属容易流失的问题,提供一种核壳结构Pt-W基催化剂及其制备方法与应用、选择性氢解反应的方法,该催化剂具有核壳结构,能够改善催化剂的活性和水热稳定性,提高目标产物选择性,减少催化剂中贵金属的流失
[0026](1)本发明的多层核壳结构催化剂以W氧化物以及Pt纳米颗粒作为活性组分,具有更加稳定的结构,以无机氧化物纳米薄膜对Pt纳米颗粒的固定作用,避免贵金属Pt组分的聚集和流失,避免催化剂活性降低,在第二层壳层外包覆最外层壳层,形成分散均匀的W活性位点;
Smart Images

Figure CN122999188A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst material synthesis, specifically to a core-shell structured Pt-W-based catalyst, its preparation method and application, and a method for selective hydrogenolysis reaction. Background Technology
[0002] 1,3-Propanediol, 1,5-Pentanediol, and 1,6-Hexanediol are important chemical intermediates and key monomers for the synthesis of high-end polyesters. Currently, the industrial production of 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol mainly uses petroleum refining, which has problems such as high energy consumption, non-renewable raw materials, difficulty in separating reaction products, and environmental pollution.
[0003] Biomass is a renewable, low-carbon resource with advantages such as wide distribution, large reserves, environmental friendliness, and zero greenhouse gas emissions, making it an attractive development prospect and one of the most promising new energy sources that can partially replace fossil fuels. Fortunately, bio-based platform compounds such as glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol can be selectively hydrogenated to secondary hydroxyl groups via Pt-W-based catalysts, thereby synthesizing 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol with high selectivity, respectively.
[0004] A method for the catalytic conversion of glycerol to 1,3-propanediol was reported in the literature (Chinese Journal of Catalysis, 2020, 41, 1261-1267), and the stability of the Pt-W-based catalyst was investigated after 700 hours of continuous operation in a fixed-bed reactor. After 700 hours of reaction, the glycerol conversion decreased from the initial 58% to 25%, and the loss of the precious metal Pt content reached 8.7 wt%.
[0005] The literature (ACS Catal. 2018, 8, 1427-1439) reports a method for selective hydrogenolysis of tetrahydrofurandiethanol to 1,6-hexanediol using a Pt-W-based catalyst, with a 1,6-hexanediol yield of up to 70%. However, the Pt content is as high as 10%, and no reports on catalyst stability have been found.
[0006] The literature (Catalysis Today, 2018, 303, 207-212) reports a method for selective hydrogenolysis of tetrahydrofurfural to 1,5-pentanediol using a Pt-W-based catalyst. The maximum yield of 1,5-pentanediol is 43%, with a Pt content of 3%. No reports on catalyst stability have been found.
[0007] Although Pt-W groups exhibit excellent activity in the conversion of bio-based platform molecules such as glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandimethyl alcohol into high-value-added terminal hydroxyl diols, problems such as rapid decrease in catalyst activity, difficulty in catalyst recycling, and excessively high costs still hinder the industrial application of such reactions. Summary of the Invention
[0008] The purpose of this invention is to overcome the problems of poor catalyst reactivity and hydrothermal stability, low target product selectivity, and easy loss of precious metals in existing technologies. This invention provides a core-shell structured Pt-W-based catalyst, its preparation method and application, and a method for selective hydrogenolysis. This catalyst has a core-shell structure, which can improve the catalyst activity and hydrothermal stability, increase the target product selectivity, and reduce the loss of precious metals in the catalyst.
[0009] To achieve the above objectives, the first aspect of the present invention provides a core-shell structured Pt-W-based catalyst, wherein the catalyst has a core-shell structure, comprising a core, a first shell layer, a second shell layer, and an outermost shell layer;
[0010] The core of the catalyst comprises heat-resistant inorganic oxides and / or molecular sieves, the first shell comprises Pt nanoparticles, the second shell comprises inorganic oxide nanofilms, and the outermost shell comprises W oxides.
[0011] Preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide.
[0012] Preferably, the average particle size of the Pt nanoparticles is 0.5-6 nm, and more preferably 2-4 nm.
[0013] Preferably, the Pt nanoparticles comprise 0.3-4% by weight, more preferably 0.8-3% by weight, based on the total weight of the catalyst.
[0014] Preferably, the inorganic oxide nanofilm of the second shell layer comprises a nanofilm composed of at least one of silicon oxide, titanium oxide, cerium oxide, and zirconium oxide.
[0015] Preferably, the thickness of the inorganic oxide nanofilm is 1-100 nm, and more preferably 5-50 nm.
[0016] Preferably, the content of W oxide in the outermost shell layer is 0.3-10% by weight, preferably 3-8% by weight, based on the total weight of the catalyst.
[0017] A second aspect of the present invention provides a method for preparing a core-shell structured Pt-W-based catalyst, wherein the method includes the following steps:
[0018] (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct;
[0019] (2) A mixture containing the first preproduct, oxide precursor and solvent is subjected to in-situ growth reaction and calcination to obtain a second preproduct with an inorganic oxide nanofilm coated on the surface of the first preproduct.
[0020] (3) W oxide was loaded onto the surface of the second preproduct and subjected to heat treatment to obtain a core-shell structured Pt-W-based catalyst.
[0021] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0022] The fourth aspect of the present invention provides the application of the catalyst described in the first or third aspect in a hydrogenolysis reaction.
[0023] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.
[0024] Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol.
[0025] The beneficial effects achieved through the above technical solution are as follows:
[0026] (1) The multilayer core-shell structure catalyst of the present invention uses W oxide and Pt nanoparticles as active components, which has a more stable structure. The inorganic oxide nanofilm fixes the Pt nanoparticles, avoiding the aggregation and loss of the noble metal Pt component and avoiding the reduction of catalyst activity. The outermost shell layer is wrapped around the second shell layer to form uniformly dispersed W active sites.
[0027] (2) In this invention, preferably, the preparation method of the catalyst is controllable. When the above catalyst is used for selective hydrogenolysis reaction, it is applied to the synthesis of 1,3-propanediol, 1,5-pentanediol and 1,6-hexanediol from glycerol, tetrahydrofurfuryl alcohol and tetrahydrofurandiethanol. The target product selectivity is high and the stability of the catalyst during long-term operation can be significantly improved. Attached Figure Description
[0028] Figure 1 This is a scanning electron microscope image of the catalyst in Comparative Example 1 without oxide nanofilm coating;
[0029] Figure 2 This is a scanning electron microscope image of the catalyst with a multilayer core-shell structure from Example 1. Detailed Implementation
[0030] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0031] The first aspect of the present invention provides a core-shell structured Pt-W-based catalyst, wherein the catalyst has a core-shell structure, comprising a core, a first shell layer, a second shell layer, and an outermost shell layer;
[0032] The core of the catalyst comprises heat-resistant inorganic oxides and / or molecular sieves, the first shell comprises Pt nanoparticles, the second shell comprises inorganic oxide nanofilms, and the outermost shell comprises W oxides.
[0033] The catalyst provided by this invention has a core-shell structure. Pt nanoparticles are loaded on the surface of the core to form a first shell layer that enhances the catalyst's reactivity. An inorganic oxide nanofilm is coated on the surface of the first shell layer to form a second shell layer, which improves the catalyst's hydrothermal stability. This avoids exposing the active sites to the outer surface of the catalyst support. When reacting at high temperatures in the aqueous phase, it reduces the loss and aggregation of the noble metal Pt active component, thus preventing a decrease in catalyst activity. An outermost shell layer is coated on the second shell layer to form uniformly dispersed W active sites.
[0034] According to the present invention, the type and source of the heat-resistant inorganic oxide are not particularly limited; it can be commercially available or prepared using existing methods, and can be a conventional heat-resistant inorganic oxide in the art, serving as a core carrier. Preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide.
[0035] According to the present invention, the type and source of the molecular sieve are not particularly limited, and it can be commercially available or prepared using existing methods. Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve, and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve. In the present invention, the silicon-aluminum molar ratio (SiO2 / Al2O3) of the molecular sieve is not particularly limited, but is preferably 5-200, and more preferably 10-100.
[0036] According to the present invention, preferably, the average particle size of the kernel is 0.1-10 μm, more preferably 0.2-2 μm. In the present invention, the average particle size of the kernel refers to the average particle size of the kernel particles, which can be a single particle or a particle aggregate formed by the aggregation of several small particles.
[0037] In this invention, the average particle size of the kernel is measured using scanning electron microscopy (SEM). The average value is obtained by randomly measuring the size of 100 kernel particles using NanoMeasurer software. During the measurement process, the average particle size has the conventional interpretation in the art, referring to the particle size; for spherical particles, it refers to the diameter of the sphere; for irregular particles, it refers to the maximum straight-line distance within the particle.
[0038] According to a preferred embodiment of the present invention, the core is selected from at least one of silica, Beta molecular sieve and USY molecular sieve.
[0039] According to the present invention, preferably, the average particle size of the Pt nanoparticles is 0.5-6 nm, for example, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, or any range between the two, preferably 2-4 nm. In the present invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the average value is taken from the particle size of 100 randomly measured Pt nanoparticles in the TEM image.
[0040] In this invention, the average particle size of the Pt nanoparticles meets the above-mentioned range limit, the Pt nanoparticles have better loading stability, can be uniformly dispersed on the core surface, and improve the catalytic activity of the catalyst.
[0041] According to the present invention, preferably, the mass percentage of Pt nanoparticles, based on the total weight of the catalyst, is 0.3-4 wt%, for example, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any range between the two, preferably 0.8-3 wt%, more preferably 0.8-1.8 wt%. In the present invention, the mass percentage of Pt nanoparticles is obtained by ICP testing.
[0042] According to the present invention, preferably, the inorganic oxide nanofilm of the second shell layer comprises a nanofilm composed of at least one of silicon oxide, titanium oxide, zirconium oxide and cerium oxide.
[0043] According to the present invention, preferably, the thickness of the inorganic oxide nanofilm is 1-100 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any range between the two, preferably 5-50 nm. In this invention, the inorganic oxide nanofilm forms a stable shell layer, fixing the Pt nanoparticles and preventing the loss of Pt nanoparticles during catalyst use, which would lead to a decrease in catalyst activity and improve the hydrothermal stability of the catalyst. If the inorganic oxide nanofilm is too thin, it cannot effectively stabilize the Pt nanoparticles, and the improvement in stability is not significant; if it is too thick, it will affect the mass transfer of hydrogen and reduce catalytic activity.
[0044] In this invention, the thickness of the inorganic oxide nanofilm is obtained by transmission electron microscopy. The thickness of the inorganic oxide nanofilm at 30 random locations in the transmission electron microscope image is measured, and the average value is taken.
[0045] According to the present invention, preferably, the content of W oxide in the outermost shell layer is 0.3-10% by weight, for example, 0.3% by weight, 0.5% by weight, 0.8% by weight, 1% by weight, 1.2% by weight, 1.5% by weight, 1.8% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, 4.5% by weight, 5% by weight, 5.5% by weight, 6% by weight, 6.5% by weight, 7% by weight, 7.5% by weight, 8% by weight, 9% by weight, 10% by weight, or any range between the two, preferably 3-8% by weight. In the present invention, the mass percentage content of W oxide is determined by ICP method.
[0046] In this invention, the outermost shell of the catalyst includes W oxide, and W active sites are uniformly dispersed on the outer surface of the catalyst, which can maximize the adsorption of raw material molecules at the W active sites and improve catalytic activity.
[0047] A second aspect of the present invention provides a method for preparing a core-shell structured Pt-W-based catalyst, wherein the method includes the following steps:
[0048] (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct;
[0049] (2) A mixture containing the first preproduct, oxide precursor and solvent is subjected to in-situ growth reaction and calcination to obtain a second preproduct with an inorganic oxide nanofilm coated on the surface of the first preproduct.
[0050] (3) W oxide was loaded onto the surface of the second preproduct and subjected to heat treatment to obtain a core-shell structured Pt-W-based catalyst.
[0051] In this invention, preferably, the preparation method of the catalyst is simple to operate and the conditions are controllable. The obtained core-shell structure Pt-W-based catalyst has high catalytic activity and high hydrothermal stability, which can meet the activity and stability requirements of the catalyst for long-term operation.
[0052] According to the present invention, preferably, in step (1), the method of loading Pt nanoparticles onto the core carrier includes the following steps:
[0053] (A) A mixture containing a platinum source, a surfactant and a solvent is heated under reflux to obtain a colloidal solution of Pt nanoparticles;
[0054] (B) The core carrier was added to the colloidal solution of Pt nanoparticles, and the solid product was obtained by solid-liquid separation and then dried to obtain the first preproduct.
[0055] According to the present invention, the type of platinum source is not particularly limited and can be any conventional platinum-containing compound that can provide Pt in the art. Preferably, the platinum source is selected from at least one of chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate.
[0056] According to the present invention, preferably, the amount of platinum source added, calculated in terms of Pt element, is 0.3-4% by weight of the total weight of the catalyst, preferably 0.8-3% by weight, and more preferably 0.8-1.8% by weight.
[0057] According to the present invention, preferably, the amount of platinum source added is calculated based on Pt element, and the weight ratio of platinum source: surfactant: solvent in step (A) is 1:(5-50):(500-10000), preferably 1:(10-30):(1000-5000).
[0058] In this invention, the surfactant is a conventional surfactant in the art, preferably selected from at least one of polyvinylpyrrolidone (PVP), copolyvinylpyrrolidone (PVP / VA), and polyvinyl alcohol (PVA).
[0059] In this invention, the type of solvent is not particularly limited. Preferably, the solvent is selected from at least one of methanol aqueous solution, ethanol aqueous solution and propanol aqueous solution. More preferably, the solvent is ethanol aqueous solution and / or propanol aqueous solution, and the volume ratio of ethanol to water and the volume ratio of propanol to water are each independently 1:0.1-2.
[0060] In this invention, the method of obtaining the mixture is not particularly limited. According to a specific embodiment of the invention, a platinum source, a surfactant, and a solvent are mixed and stirred at room temperature to obtain a mixture. The stirring rate and stirring time are not particularly limited, and those skilled in the art can make adaptive adjustments.
[0061] According to the present invention, preferably, the conditions for heating reflux include: under a protective atmosphere, a heating temperature of 60-180°C, preferably 80-160°C, and a heating time of 0.5-6 hours, preferably 1-5 hours.
[0062] In this invention, the type of protective atmosphere is not particularly limited, but is preferably selected from at least one of argon, nitrogen and helium.
[0063] According to the present invention, preferably, the core carrier comprises heat-resistant inorganic oxides and / or molecular sieves.
[0064] According to the present invention, preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide and silicon dioxide.
[0065] According to the present invention, preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve, and USY molecular sieve, and more preferably from Beta molecular sieve and / or USY molecular sieve. The type and source of the core carrier have been described in the foregoing specification and will not be repeated here.
[0066] In this invention, preferably, step (B) further includes adding acetone or tetrahydrofuran to the core support and the colloidal solution of Pt nanoparticles, mixing, and then performing solid-liquid separation. The volume ratio of acetone or tetrahydrofuran to the solvent in step (A) is 1-8:1. Adding acetone can adjust the solubility of Pt nanoparticles in the solution, thereby promoting the uniform loading of Pt nanoparticles on the support.
[0067] In this invention, the method of solid-liquid separation is not particularly limited, but filtration is preferred. The drying conditions are not particularly limited; obtaining a dried first pre-product is sufficient. Preferably, the drying temperature is 80-120℃ and the drying time is 6-12 hours.
[0068] According to the present invention, preferably, in step (2), the conditions of the in-situ growth reaction include: a reaction temperature of 20-40℃, preferably 25-35℃; and a reaction time of 1-6h, preferably 2-5h.
[0069] According to the present invention, preferably, the mass ratio of the oxide precursor to the first preproduct, based on oxides, is 0.1-1.5:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.4:1, 1.5:1, or any range between the two, preferably 0.5-1:1.
[0070] According to the present invention, preferably, the oxide precursor is selected from at least one of silicon source, titanium source, cerium source and zirconium source.
[0071] In this invention, the silicon source is a conventional silicon source in the art, capable of generating silicon oxide nanofilms through in-situ growth. Preferably, the silicon source is tetraethyl orthosilicate and / or methyl orthosilicate.
[0072] In this invention, the titanium source is a conventional titanium source in the art, which can be used to generate a titanium oxide nanofilm after in-situ growth. Preferably, the titanium source is at least one of titanium silicate and / or titanium sulfate.
[0073] In this invention, the zirconium source is a conventional zirconium source in the art, which can generate a zirconium oxide nanofilm after in-situ growth. Preferably, the zirconium source is zirconium n-butoxide and / or zirconium tetra-tert-butoxide.
[0074] In this invention, the cerium source is a conventional cerium source in the art, preferably cerium sulfate.
[0075] In this invention, preferably, the in-situ growth reaction in step (2) further includes the addition of an optional alkali source. The type of alkali source is not particularly limited, and it is a conventional alkaline compound in the art, preferably selected from at least one of ammonia, sodium hydroxide, and potassium hydroxide. The addition of the above-mentioned alkali source can facilitate the hydrolysis of the oxide precursor and promote the growth of inorganic oxide nanofilms.
[0076] In this invention, the amount of alkali source added is not particularly limited, the amount of oxide precursor added is based on oxide, and the weight ratio of alkali source to oxide precursor is 0.01-0.5:1, preferably 0.02-0.1:1.
[0077] In this invention, the type and amount of solvent added in step (2) are not particularly limited. Preferably, the solvent is selected from at least one of water, ethanol, and propanol, preferably water and ethanol, with a volume ratio of ethanol to water of 1:0.1-2. Preferably, the amount of solvent added is 10-100 mL relative to 1 g of the first preproduct.
[0078] In this invention, preferably, the in-situ growth reaction in step (2) is not particularly limited. According to a specific embodiment of the invention, the first preproduct is dispersed in a solvent, and an oxide precursor and an optional alkali source are added.
[0079] In this invention, step (2) further includes calcining the in-situ growth reaction product after solid-liquid separation following the completion of the in-situ growth reaction.
[0080] According to the present invention, preferably, in step (2), the calcination conditions include: a temperature of 200-800℃, preferably 300-600℃; and a time of 1-10h, preferably 3-6h. In this invention, calcination yields a second preproduct coated with an inorganic oxide nanofilm on the surface of the first preproduct. This preproduct fixes the Pt nanoparticles supported on the core carrier, inhibiting the loss and aggregation of the noble metal Pt during catalyst use and improving the long-term operational stability of the catalyst.
[0081] According to the present invention, preferably, the thickness of the inorganic oxide nanofilm is 1-100 nm, more preferably 5-50 nm.
[0082] In this invention, the method of loading W oxide onto the surface of the second preproduct is not particularly limited. According to a preferred embodiment of the invention, an equal-volume impregnation method is used, which includes: mixing the second preproduct with a solution containing a tungsten precursor and then drying it.
[0083] In this invention, the tungsten precursor is a conventional tungsten-containing compound in the art, preferably selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate.
[0084] In this invention, the concentration of the solution containing the tungsten precursor is not particularly limited, and those skilled in the art can adjust it adaptively according to the W oxide loading.
[0085] In this invention, the drying conditions are not particularly limited, and those skilled in the art can adapt the drying conditions according to the drying situation. Preferably, the drying temperature is 80-120℃ and the drying time is 6-12 hours.
[0086] According to the present invention, preferably, the heat treatment conditions include: a heat treatment temperature of 100-800℃, preferably 500-600℃; and a heat treatment time of 1-10h, preferably 2-6h.
[0087] According to the present invention, preferably, the weight ratio of the W oxide to the second preproduct is 0.003-0.11:1, more preferably 0.03-0.087:1. The amount of tungsten precursor added is sufficient to ensure that the weight ratio of the W oxide to the second preproduct meets the above range.
[0088] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0089] The fourth aspect of the present invention provides the application of the catalyst described in the first or third aspect in a hydrogenolysis reaction.
[0090] In this invention, the above-mentioned catalyst, when applied to hydrogenolysis, can significantly reduce the loss of precious metal Pt, slow down the rate of catalyst activity reduction, improve the long-term operational stability of the catalyst, and reduce the cost required for hydrogenolysis, making it suitable for industrial applications of hydrogenolysis.
[0091] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.
[0092] According to the present invention, preferably, the reaction raw materials are selected from at least one of glycerol, tetrahydrofurfuryl alcohol and tetrahydrofurandiethanol.
[0093] In this invention, the above-mentioned catalyst is used to selectively hydrogenolyze 1,3-propanediol, 1,5-pentanediol and 1,6-hexanediol. The reaction conditions are easy to control, the catalyst has high activity, the feed conversion rate and the target product selectivity are high. After long-term operation, the loss rate of precious metal Pt in the catalyst is low, and the feed conversion rate and the target product selectivity are maintained at a high level.
[0094] According to the present invention, preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180°C, preferably 140-170°C; and a hydrogen pressure of 1-8 MPa, preferably 3-6 MPa.
[0095] According to the present invention, the apparatus for the reaction is not particularly limited; preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity of 0.05-5 h⁻¹. -1 Preferably 0.1-3h -1 .
[0096] According to a preferred embodiment of the present invention, the aqueous solution of the reactants is contacted with a catalyst to carry out a selective hydrogenolysis reaction.
[0097] In this invention, preferably, the concentration of the aqueous solution of the reaction raw materials is 10-95% by weight, more preferably 20-60% by weight.
[0098] In this invention, the liquid phase refers to the aqueous solution of the reaction raw materials.
[0099] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are commercially available, and the room temperature is 25°C.
[0100] Polyvinylpyrrolidone is Aladdin's K88-96 (average molecular weight is 1,300,000);
[0101] The Beta molecular sieve is NKF-6 from Nankai Catalyst Plant;
[0102] The polyvinyl alcohol is Aladdin's P752227.
[0103] Example 1
[0104] Catalyst A1 was prepared using the following steps:
[0105] (1-A) Measure 250 mL of water and 250 mL of ethanol as a mixed solvent and place them in a 1 L round-bottom flask. Add chloroplatinic acid solution and polyvinylpyrrolidone (PVP) to the flask, stir for 5 min, then heat to 100 °C and reflux for 3 h under an argon atmosphere to obtain a Pt nanoparticle colloidal solution. The weight ratio of platinum source, polyvinylpyrrolidone and mixed solvent, calculated as platinum element, is 1:20:3000.
[0106] (1-B) Add 10g of silica core carrier to the above Pt nanoparticle colloidal solution, add acetone, stir for half an hour, filter and separate, and dry at 100℃ for 8 hours to obtain the first preproduct.
[0107] The silica core carrier has an average particle size of 0.25 μm, and the volume of acetone is 4 times that of the Pt nanoparticle colloidal solution.
[0108] (2) Disperse 10g of the first preproduct in 100mL of ethanol aqueous solution (ethanol and water volume ratio is 1:1), add zirconium n-butoxide and ammonia, and grow in situ at room temperature for 4 hours. After filtration, calcine at 600℃ for 3 hours to obtain the second preproduct.
[0109] Among them, based on the mass of zirconium oxide, the mass ratio of zirconium dioxide to the first preproduct is 0.6:1, and the mass ratio of ammonia to the first preproduct is 0.05:1.
[0110] (3) Dissolve a certain amount of ammonium metatungstate in 12 mL of water, add 10 g of the second preproduct to the above solution and impregnate it in equal volume, stir for 10 minutes, dry at 100 °C for 8 h, and heat treat at 550 °C for 3 h to obtain the final catalyst A1.
[0111] In this case, the weight ratio of tungsten trioxide to the second preproduct is 0.05:1, based on the mass of W oxide.
[0112] Figure 2 Scanning electron microscope (SEM) images of catalysts with multi-layered core-shell structures, from Figure 1 As can be seen, the catalyst prepared in Example 1 has a distinct multilayer core-shell structure, and the thickness of the inorganic oxide nanofilm is 35 nm.
[0113] Example 2
[0114] The core-shell structured Pt-W-based catalyst A2 was prepared using the method of Example 1. The difference is that in step (2), the weight ratio of zirconium dioxide to the first preproduct was 1:1 based on the mass of zirconium oxide. The catalyst parameters are listed in Table 1.
[0115] Example 3
[0116] Catalyst A3 was prepared using the following steps:
[0117] (1) Measure 100 mL of water and 400 mL of ethanol as a mixed solvent and place them in a 1 L round bottom flask. Add platinum nitrate solution and PVA (polyvinyl alcohol) to the flask, stir for 5 min, then heat to 90 °C and reflux for 2 h under an argon atmosphere to obtain a Pt nanoparticle colloidal solution. The weight ratio of platinum source, polyvinylpyrrolidone and mixed solvent, calculated as platinum element, is 1:20:2000.
[0118] (1-B) Add 20g of Beta molecular sieve core carrier to the above Pt nanoparticle colloidal solution, add acetone, stir for half an hour, filter and separate, and dry at 120℃ for 3 hours to obtain the first preproduct.
[0119] The volume of acetone is four times that of the Pt nanoparticle colloidal solution, and the average particle size of the core carrier is 0.3 μm.
[0120] (2) Disperse 10g of the first preproduct in 100mL of ethanol aqueous solution (ethanol and water volume ratio is 1:1), add ethyl orthosilicate and ammonia, and grow in situ at room temperature for 6 hours. After filtration, calcine at 500℃ for 5 hours to obtain the second preproduct.
[0121] Among them, based on the mass of silicon oxide, the mass ratio of silicon source to first preproduct is 0.8:1, and the mass ratio of ammonia to first preproduct is 0.1:1.
[0122] (3) Dissolve a certain amount of ammonium paratungstate in 12 mL of water, add 10 g of the second preproduct to the above solution, stir for 10 minutes, dry at 100 °C for 8 h, and heat treat at 500 °C for 4 h to obtain the final catalyst A3.
[0123] In this case, the mass ratio of tungsten trioxide to the second preproduct is 0.06:1, based on the mass of W oxide.
[0124] Example 4
[0125] The core-shell structured Pt-W-based catalyst A4 was prepared using the method of Example 1, except that the amount of tungsten precursor added in step (3) was changed. The mass ratio of tungsten trioxide to the second preproduct was 0.02:1 based on the mass of W oxide. Other conditions were the same as in Example 1, and the final catalyst A4 was obtained.
[0126] Example 5
[0127] The core-shell structured Pt-W-based catalyst A5 was prepared using the method of Example 1. The difference was that in step (2), the weight ratio of zirconium dioxide to the first preproduct was 1.2:1 based on the mass of zirconium oxide, and other conditions were the same as in Example 1, to obtain the final catalyst A5.
[0128] Comparative Example 1
[0129] The core-shell structured Pt-W-based catalyst D1 was prepared using the method of Example 1, except that the entire process of step (2) was not performed, that is, the synthesized catalyst did not have a second inorganic oxide nanofilm. The catalyst parameters are listed in Table 1.
[0130] Figure 1 The image shows a scanning electron microscope (SEM) image of the catalyst in Comparative Example 1 without oxide nanofilm coating. Figure 1 As can be seen, no inorganic oxide nanofilms were observed in the catalyst of Comparative Example 1, and no multilayer core-shell structure was formed.
[0131] Comparative Example 2
[0132] A certain amount of ammonium metatungstate was dissolved in 12 mL of water. 10 g of silica support was added to the solution for equal-volume impregnation. The mixture was stirred for 10 minutes, dried at 100°C for 8 hours, and then heat-treated at 550°C for 3 hours to obtain the first preproduct. Next, the first preproduct was loaded with Pt components using an equal-volume impregnation method and calcined at 400°C for 3 hours to obtain the final catalyst D2. The loading amounts of Pt and W were the same as in Example 1.
[0133] Catalyst parameters for the examples and comparative examples are shown in Table 1.
[0134] Table 1
[0135] Catalyst number Second shell thickness / nm W oxide content / weight % Example 1 A1 35 4.99 Example 2 A2 48 4.99 Example 3 A3 42 5.98 Example 4 A4 35 1.98 Example 5 A5 59 4.97 Comparative Example 1 D1 0 4.98 Comparative Example 2 D2 0 4.99
[0136] Test Case 1-9, Comparative Test Case 1-4
[0137] Weigh 1g of the catalyst obtained above and place it in a fixed bed. Under the conditions of reaction temperature of 160℃ and hydrogen pressure of 5MPa, the reaction is carried out at a rate of 1h. -1 A 40 wt% aqueous solution of the reactants was introduced at a space velocity of [value missing]. Liquid samples were collected from the outlet at the initial stage (first 4 hours) and at 360 hours for gas chromatography analysis. Catalyst parameters and reaction results are listed in Tables 2 and 3.
[0138] Table 2
[0139]
[0140] Table 3
[0141]
[0142]
[0143] The results in Tables 1, 2, and 3 show that the catalyst prepared using this invention forms a core-shell structure. When used in the selective hydrogenolysis of secondary hydroxyl groups in oil, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol to synthesize 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol, it exhibits higher hydrothermal stability compared to the catalyst synthesized in Comparative Example 1. It can significantly suppress the loss and aggregation of precious metal Pt, reducing the Pt loss rate by more than 10 times, thus laying the foundation for promoting the industrial application of bio-based high-end glycol polyester monomers.
[0144] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A core-shell structured Pt-W-based catalyst, characterized in that, The catalyst has a core-shell structure, including a core, a first shell, a second shell, and an outermost shell. The core of the catalyst comprises heat-resistant inorganic oxides and / or molecular sieves, the first shell comprises Pt nanoparticles, the second shell comprises inorganic oxide nanofilms, and the outermost shell comprises W oxides.
2. The catalyst according to claim 1, wherein, The heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide; Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve. Preferably, the average particle size of the kernel is 0.1-10 μm, more preferably 0.2-2 μm.
3. The catalyst according to claim 1 or 2, wherein, The average particle size of the Pt nanoparticles is 0.5-6 nm, preferably 2-4 nm; Preferably, the Pt nanoparticles comprise 0.3-4% by weight, more preferably 0.8-3% by weight, based on the total weight of the catalyst.
4. The catalyst according to any one of claims 1-3, wherein, The inorganic oxide nanofilm of the second shell layer includes a nanofilm composed of at least one of silicon oxide, titanium oxide, cerium oxide, and zirconium oxide; Preferably, the thickness of the inorganic oxide nanofilm is 1-100 nm, and more preferably 5-50 nm; Preferably, the content of W oxide in the outermost shell layer is 0.3-10% by weight, preferably 3-8% by weight, based on the total weight of the catalyst.
5. A method for preparing a core-shell structured Pt-W-based catalyst, characterized in that, The method includes the following steps: (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct; (2) A mixture containing the first preproduct, oxide precursor and solvent is subjected to in-situ growth reaction and calcination to obtain a second preproduct with an inorganic oxide nanofilm coated on the surface of the first preproduct. (3) After loading W oxide onto the surface of the second preproduct and performing heat treatment, a core-shell structured Pt-W-based catalyst is obtained.
6. The preparation method according to claim 5, wherein, In step (1), the method of loading Pt nanoparticles onto the core support includes the following steps: (A) A mixture containing a platinum source, a surfactant and a solvent is heated under reflux to obtain a colloidal solution of Pt nanoparticles; (B) The core carrier was added to the colloidal solution of Pt nanoparticles, and the solid product was obtained by solid-liquid separation and then dried to obtain the first preproduct; Preferably, the core carrier comprises heat-resistant inorganic oxides and / or molecular sieves; Preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide; Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve.
7. The preparation method according to claim 6, wherein, The platinum source is selected from at least one of chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate. Preferably, the amount of platinum source added, calculated as Pt element, is 0.3-4% by weight of the total weight of the catalyst, preferably 0.8-3% by weight. Preferably, the amount of platinum source added is calculated based on Pt element, and the weight ratio of platinum source: surfactant: solvent in step (A) is 1:(5-50):(500-10000), preferably 1:(10-30):(1000-5000). Preferably, the heating reflux conditions include: under a protective atmosphere, a heating temperature of 60-180℃, preferably 80-160℃, and a heating time of 0.5-6h, preferably 1-5h.
8. The preparation method according to claim 5, wherein, In step (2), the conditions for the in-situ growth reaction include: a reaction temperature of 20-40℃, preferably 25-35℃; and a reaction time of 1-6h, preferably 2-5h. Preferably, in step (2), the calcination conditions include: a temperature of 200-800℃, preferably 300-600℃; and a time of 1-10h, preferably 3-6h. Preferably, the weight ratio of the oxide precursor to the first preproduct, based on oxides, is 0.1-1.5:1, more preferably 0.5-1:1; Preferably, the oxide precursor is selected from at least one of silicon source, titanium source, cerium source and zirconium source; Preferably, the thickness of the inorganic oxide nanofilm is 1-100 nm, and more preferably 5-50 nm.
9. The preparation method according to claim 5, wherein, The heat treatment conditions include: a heat treatment temperature of 100-800℃, preferably 500-600℃; and a heat treatment time of 1-10h, preferably 2-6h. Preferably, the weight ratio of the W oxide to the second preproduct is 0.003-0.11:1, more preferably 0.03-0.087:
1.
10. The catalyst prepared by the method according to any one of claims 5-9.
11. The use of the catalyst according to any one of claims 1-4 and 10 in hydrogenolysis reactions.
12. A method for selective hydrogenolysis, characterized in that, The method comprises: selectively hydrogenating the reactants in the presence of the catalyst described in any one of claims 1-4 and 10; Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol. Preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180℃, more preferably 140-170℃; and a hydrogen pressure of 1-8 MPa, more preferably 3-6 MPa. Preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity (LHSV) of 0.05-5 h⁻¹. -1 Preferably 0.1-3h -1 .
